The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.5194/hess-8-1164-2004
|View full text |Cite
|
Sign up to set email alerts
|

Using stable isotopes of water to infer wetland hydrological dynamics

Abstract: This paper considers the potential of oxygen and hydrogen isotope ratios to identify spatial and temporal changes in the water source of a lowland headwater wetland situated adjacent to the River Tern in Shropshire, UK. Stable isotope composition (d 18 O) of end-members varied between 7.5 and 8.0 for groundwater, 7.3 and 8.5 for river-water and 4.5 and 8.0 for precipitation. Water samples were extracted from six nests each comprising three porous cup samplers at depths of 0.2 m, 0.5 m and 1.0 m between June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 14 publications
0
14
0
2
Order By: Relevance
“…3). Studies of the stable isotope composition (Clay et al, 2004) and borehole pumping tests (Allen et al, 1997) have indicated that the River Tern derives much of its flow from groundwater. The nearest flow gauging station is approximately 2.5 km upstream of the study reach (at Ternhill, national grid reference SJ 629 316), operated by the Environment Agency.…”
Section: Description Of Field Site and Installationmentioning
confidence: 98%
“…3). Studies of the stable isotope composition (Clay et al, 2004) and borehole pumping tests (Allen et al, 1997) have indicated that the River Tern derives much of its flow from groundwater. The nearest flow gauging station is approximately 2.5 km upstream of the study reach (at Ternhill, national grid reference SJ 629 316), operated by the Environment Agency.…”
Section: Description Of Field Site and Installationmentioning
confidence: 98%
“…The sampling is relatively easy and, therefore, suitable for remote areas. However, few studies have been undertaken to use stable water isotopes for the investigation of hydrological processes in wetlands (Clay et al 2004).…”
mentioning
confidence: 99%
“…Variation in stable isotope composition can classify patterns of groundwater recharge and flow and have been used to estimate groundwater residence time (Soulsby et al, 2000). Isotopes have also been used to investigate the seasonal dynamics in wetland water storage (Clay et al, 2004). However, comparatively few studies have used isotope to determine groundwater sources of inland wetland, to discriminate sources of groundwater recharge and to understand mixing and contamination processes of groundwater.…”
Section: Introductionmentioning
confidence: 99%